STRATEGY IN DEVELOPING HUMAN RESOURCE COMPETENCY IN VUCA WORLD ERA (A Case Study in PPSDM Ministry of Home Affairs Makassar Region) - T R Fahsul Falah (International Journal of Social Science, 2021)
Human Resources (HR) is one of the crucial factors which cannot be separated from an organization. In this era, developing HR is in VUCA World (Volatile, Uncertain, Complex, Ambiguous) is a challenge that an institution must deal with. State Civil Apparatus competency development institute, particularly in the Ministry of Home Affairs, is PPSDM in Makassar Region. The strategy for developing competency in the VUCA world era is a vital task. The method used in this research is literary study, while the research location is in PPSDM of the Ministry of Home Affairs Makassar Region. The present research result is that the correct strategy to develop state civil apparatus competency corresponding to Coronavirus Pandemic is to employ digital service (digitalization) through optimizing institutional and program activities to face the VUCA world. This method was applied to support LMS (Learning Management System) in PPSDM of the Ministry of Home Affairs Makassar Region creatively and innovatively. It is supported by a synergic inter-institutional managerial system and learning organization; subsequently, it holds on training rate indicator concept and learning concepts corresponding to the current circumstances by involving all stakeholders.